Gold and its Determining Role in Modernization and Technological Processes Related to Changing Geo-economic Structure of the World - Dudin, Mihail Nikolaevich; Sekerin, Vladimir Dmitriyevich; Gorohova, Anna Evgenevna; Gayduk, Vladimir Ivanovich; Danko, Tamara Petrovna (International Journal of Economics and Financial Issues, 2016)
This article considers the role of gold in the world economy and its place in contemporary structures of gold-value reserves of the leading countries of the world. It also takes into account the historical experience of using gold in various periods (epochs). The theme of the article is rather urgent at the moment of transformation and occurrence of a new transitional stage in the world economy, because traditionally at any transitional period the investment activity was focused on the least risky investments. Investments in precious metals are thought to be such investments. They do not lose their value and price during the long period of time. The following essential conclusions were received within this article: 1) Gold is the most demanded precious metal in terms of decreasing risks of accumulation and investments. The main part of the gold obtained industrially is presented by centralized reserves (standard ingots of chemically pure gold). 2) Gold mining is limited in the world because natural reserves of this metal are irretrievable; at the same time modern physical and chemical technologies allow to artificially grow crystals of gold; however, such technologies are characterized by high cost and low level of returns from their use. 3) Gold as a resource will continue playing a psychologically stabilizing role; herewith, the information resource (business information) required for ensuring the world stable social and economic development will get basic value. Keywords: gold, gold and foreign currency reserves, economic crisis, factorial analysis, cluster analysis. JEL Classifications: Q32, Q34, H54, P45